Technology Used at Home for Children with Complex Needs The Identification of the Types of Technology used by Children with Complex Needs at Home. - NICHOLL, HONOR (Trinity College Dublin, 2012)
This exploratory mixed method study was undertaken to identify the types of technology used in the care of young children with complex needs at home. A number of major factors underpinned the need for this study. Internationally and nationally there is an increasing emphasis on providing children’s palliative care services and on sustaining their excellence and quality (European Association of Palliative Care (EAPC) (2009) & Department of Health and Children (DoH&C) (2010)).Children’s palliative care includes providing care for children with complex needs and life limiting illnesses in which technological care giving forms part of mother’s caring roles (Nicholl 2008). However the exact nature of this technology and its use in the family home is under researched. The aim of the study was: to identify the types of technology used by children with complex needs receiving their care from their parents at home. The study’s objectives were: to identify the equipment used at home in the children’s care. to identify parents’ concerns regarding equipment used in the home. The study was conducted in two phases. Data was collected from nurses and parents caring for their children at home. In Phase 1 registered children’s nurses (RCNs) were invited to participate in a focus group interview and in Phase 2 parents were invited to complete a questionnaire.
PUBLISHED
School of Nursing and Midwifery